Development of a methodology of optimization and fixing prices of Hardwood Exports from U.S. to Europe and Asia - Brenes-Ramírez, Diana (2014)
This work is about the development of a methodology of optimization and fixing prices of Hardwood Exports from U.S. to Europe and Asia. The approach emphasizes on creating a methodology that allows the companies to set prices for their products from concrete bases where this considered internal and external factors , in addition to comply with the customer expectations . The opportunity for this improvement comes after the domestic market crisis in Europe and Asia in 2009, specifically for 2013 when the hardwood exports increased considerably and this is considered like a key for companies improve them performance in exports. The methodology is based on the principles of “Revenue Management” which is a theory that predicts consumer behavior and seeks to optimize prices to maximize revenue of the company. The objective of maximizing total contribution margin of the company is achieved by applying the theory PRO ( Pricing and Revenue Optimization) which provides a consistent and concrete approach to pricing decisions throughout the organization also seeks represent the price as a process worthy of being continuously improved . By the negative association between price and demand and with the equation that describes this relation it is introduced into the equation of total contribution margin that is maximized for obtain the optimal price.